Physicochemical Treatment Of Stabilized Landfill Leachate Using Electroflotation And Iron Oxide Nanoparticles Coagulation - Shadi, Abdubaki Mohamed Hussen (2022)
Landfill leachate is a significant source of organic and inorganic pollutants due to extremely high volumes of waste and low levels of hazardous substances. This study investigates the treatability of removing Chemical oxygen demand (COD), Ammoniacal Nitrogen (NH3-N) and color from landfill leachate by iron oxide nanoparticles (Fe2O3) coupled electroflotation process. Stabilized landfill leachate samples were collected from Pulau Burung Landfill Site (PBLS), Penang, Malaysia and characterized. The preparation of iron oxide nanoparticle was through a simple method of mechanical milling process into nanoparticles. Five steps were used for the preparation of iron oxide nanoparticles. Adsorption studies were used one factor at a time to determine the maximum conditions of the operational parameters. All the experiments were carried out at laboratory scale using 250 mL Erlenmeyer flask as batch reactors. pH, dose, contact time and temperature were used as individual factors with pH (2-10), dose (5-30 g/L), contact time (10-60 min) and temperature (RT- 80 ℃). In contrast, the electroflotation process was prepared for the post treatment of landfill leachate.